Bienestar y políticas familiares en España - Moreno, Luis; Salido, Olga (Política y Sociedad, 2008)
The article analyses recent development in families and social policy-making. First, a succinct review is carried out on programmes and policies since the times of transition to democracy (late 1970s). Subsequently, political initiatives and legislation put forward by PP (1996-2004) and PSOE (2004- ) Governments are examined contrasting the approaches taken by both main Spanish parties. Among the concluding remarks it is pointed out that the articulation of a framework for family protection is still pending in Spain’s social protection system. It should guarantee the universal individual rights of family members and uphold the primary social function that families provide for social welfare.